FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA HIPERTENSI PADA LANSIA DI PUSKESMAS III DENPASAR UTARA TAHUN 2012 - Ratna Wulandari; Kadek Agus Dwija Putra; I Wayan Sandi (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2018)
Background: The prevalence of isolated systolic hypertension (HST) is expected to occur approximately 25% in the age group of 60-90 years, and found as much as 59.1% in males and 61.9% in females. This research aims to determine the factors related to the incidence of hypertension in the elderly. Methods: This study uses a descriptive analytical design with the Cross Sectional approach. The research samples used are seniors aged ? 60 years and older with Consecutive Sampling technique in the working area of Puskesmas III North Denpasar. Data retrieval takes place from April to May 2012 by filling out questionnaires, measuring weight, height and blood pressure. The Data obtained is analyzed univariate and bivariate using Chi-Square test. Results: Based on the analysis gained that the factors associated with the occurrence of hypertension in the elderly are The age factor (OR: 10,833; 95% CI: 1,961-59,834), Gender factor (OR: 7,467; 95% CI: 1,400-39,837), Genetic factor (OR: 10,083; 95% CI: 1,658-61,330), Activity factors (OR: 0,095; 95% CI: 0,017-0,529), and the habit of drinking coffee (OR: 15,556; 95% CI: 2,586-93,571). Conclusion: Age, gender, genetic, activity and coffee habits are factors related to hypertension in the elderly. Expected parties are more promoting health programs in the elderly, especially on hypertensive diseasesKeywords: hypertension; elderly; activities; drinking coffee